Copyright future, copyright freedom : marking the 40th anniversary of the commencement of Australia's Copyright Act 1968 - Fitzgerald, Brian F.; Atkinson, Benedict A. C. (Sydney University Press, 2011)
This volume offers the thinking and suggestions of some of the finest minds grappling with the future of copyright regulation.